2014
DOI: 10.1002/fsn3.87
|View full text |Cite
|
Sign up to set email alerts
|

Lytic enzyme production optimization using low‐cost substrates and its application in the clarification of xanthan gum culture broth

Abstract: Lytic enzymes are widely used in industrial biotechnology as they are able to hydrolyze the bacterial cell wall. One application of these enzymes is the clarification of the culture broth for the production of xanthan gum, because of its viability in viscous media and high specificity. The screening process for filamentous fungi producing lytic enzymes, the optimization of production of these enzymes by the selected microorganism, and the optimization of the application of the enzymes produced in the clarifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…zinniae (Sun, 1991), Xanthomonas sp. (Silva et al, 2014), and Xanthomonas campestris (Dow et al, 1993). Recently, proteolytic enzyme was characterized from Xanthomonas campestris pv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…zinniae (Sun, 1991), Xanthomonas sp. (Silva et al, 2014), and Xanthomonas campestris (Dow et al, 1993). Recently, proteolytic enzyme was characterized from Xanthomonas campestris pv.…”
Section: Resultsmentioning
confidence: 99%
“…punicae strain has the ability to produce xylanolytic and cellulolytic enzymes (Amat et al, 2014). Lytic enzyme was produced from Xanthomonas campestris using low cost substrates (Da Silva et al, 2014). Kalashnikova et al (2003) used three Xanthomonas campestris pv.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that lytic enzymes (protease, glucanase and chitinase) acted synergistically to digest the cell wall of C. albicans [1]and this effect started with protease which cleave cell wall protein and open it to expose the inner layer of glucan and chitin to be attacked by glucanase and chitinase forming a big hole in the cell wall giving a protoplast which can be lyses immediacy releasing the cell constituents [3]. Thus this multi-enzyme system can be applied for biological control [4,40].…”
Section: Study Of Mode Of Action By Testing Cell Wall Integritymentioning
confidence: 94%
“…The cell wall of gram-negative bacteria is composed of a peptidoglycan layer surrounded by an outer membrane, consisting mainly of proteins, phospholipids, lipoproteins and lipopolysaccharides (da Silva et al, 2012). Gram-negative bacteria are resistant to enzymatic lysis by lytic enzymes that hydrolyse only the peptidoglycan layer, such as lysozymes and murein hydrolases.…”
Section: Downstream Separation and Purification Of Phamentioning
confidence: 99%
“…Therefore, the effective lysis of the cell wall of gram-negative bacteria can be accomplished by the combination of various enzymes, such as amidase, lipase and protease. Filamentous fungi can produce a combination of enzymes required for the lysis of the cell wall of gram-negative bacteria (da Silva et al, 2012). Tsakona et al (2016) showed that crude enzymes preparation produced via solid state fermentation of Aspergillus awamori could be used for the lysis of oleaginous yeast cells leading to the release of microbial oil that is originally produced as an intracellular product.…”
Section: Downstream Separation and Purification Of Phamentioning
confidence: 99%